One‐Pot Synthesis of CdSe Quantum Dots in Aqueous Solution for Biological Labeling. Issue 11 (26th July 2013) - Dong, Meiting; Fu, Shasha; Liu, Shuxian; Xu, Jingyi; Huang, Chaobiao
Abstract The one‐pot synthesis of water‐soluble and biologically compatible yellow CdSe quantum dots (QDs) featuring the use of glutathione (GSH) as the capping and reducing agent was achieved under aqueous conditions at 150 °C. The synthesized yellow CdSe QDs with quantum yield (QY) up to 20% exhibit zinc blende cubic structure particles with an average diameter of 4‐5 nm. It was found that both molar ratio of Se/Cd and reaction time had a significant effect on size distribution of GSH‐CdSe QDs. Meanwhile, the interaction of QDs bioconjugated to bovine hemoglobin (BHb) was studied by absorption and fluorescence(FL) spectra. With addition of BHb, the FL intensity of CdSe QDs largely quenched due to the static mechanism. The linear range is 5.0 × 10−8 mol/L to 3.0 × 10−6 mol/L, and the correlation coefficient is 0.9991, suggesting that could be used as a probe to label biological molecules and bacterial cells.